The way I am now - Smith, Amber, 1982-; Smith, Amber, 1982- (New York : Margaret K. McElderry Books, 2023)
Eden and Josh reunite as Eden's rape case goes to trial, testing the strength of their relationship amidst the challenges of college life and Eden's pursuit of justice.
Ages 14 up.
Grades 10-12.
Keywords: Interpersonal relations -- Fiction; Dating -- Fiction; Trials -- Fiction; Emotional problems -- Fiction